The Impact of E-Commerce, Exchange Rates, and Interest Rates on Indonesia's Economic Growth - Syafa Maytara Sultri Mulza; Muhammad Wakhid Musthofa; Muhammad Ghafur Wibowo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The rapid development of e-commerce transactions in Indonesia plays an important role in driving economic growth in Indonesia, especially amidst changes in exchange rates and interest rates that affect the overall economic situation. However, there have not been many studies that examine the influence of these three variables simultaneously using quarterly time series data. Therefore, this research is intended to be able to examine the impact of e-commerce transactions, exchange rates, and interest rates on Indonesia's economic growth during the quarterly period of 2011 to 2024. The method applied is multiple linear regression with the Ordinary Least Squares (OLS) method on time series data, accompanied by classical assumption tests such as autocorrelation, normality, heteroscedasticity, and multicollinearity tests to ensure the validity of the model using Eviews 12 software. The results of the study indicate that e-commerce transactions, exchange rates, and interest rates simultaneously (together) and partially (separately) have a positive and significant effect on economic growth. The resulting regression model had an R-square value of 98.7%, indicating excellent ability to explain variations in economic growth. Therefore, it can be concluded that these results form the basis for recommendations that must be analyzed holistically for digital technology integration policies through e-commerce and responsive monetary policy, which are key factors in supporting sustainable economic growth in Indonesia. These findings are expected to serve as a reference for policymakers in formulating economic strategies to remain adaptive to technological developments and macroeconomic conditions.